Optimalisasi Pengolahan Bahan Pustaka dan Temu Balik Informasi melalui Sistem Otomasi SLiMS di Perpustakaan Politeknik STIA LAN Makassar - Ma'duni, Muhammad Rusydi Tajussabirin; Sarmila, Sarmila; Chairunnisa , Siti; Habsyi, Sitti Husaebah Pattah; Umar, Touku; Abidin, Saenal (Al Mu'azarah: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to optimize library material processing and information retrieval strategies at the STIA LAN Makassar Polytechnic Library through the implementation of the SLiMS automation system. The initial problems included incomplete bibliographic data, entries, and mismatches between book locations and the system records. The activity was carried out through a one-month field practice consisting of several stages, including ownership stamping, inventory recording, classification, data input into SLiMS, label printing, and collection arrangement. As a result, all donated collections were successfully processed with complete supporting metadata, the automation system became more accurate, and collections were easier to locate. This activity also enhanced the skills of librarians and students in technology-based information management.